Visualising Multilingual Lives: More Than Words Paula Kalaja and Silvia Melo-Pfeifer (eds) (2019). (20th December 2021) - Tan, Peter
Abstract : Visualising Multilingual Lives: More Than Words Paula Kalaja and Silvia Melo-Pfeifer (eds) (2019) Bristol: Multilingual Matters. Pp. 312 ISBN-13: 978-1-78892-260-9 (hbk) ISBN-13: 978-1-78892-259-3 (pbk)